Augmentative and alternative communication for children with autism spectrum disorder: an evidence-based evaluation of the Language Acquisition through Motor Planning (LAMP) programme - Bedwani Naguib, Mary-Anne; Bruck, Susan; Costley, Debra (Cogent OA, 2015)
Children diagnosed with autism spectrum disorder often have restricted verbal communication. For children who do not use functional speech, augmentative and alternative communication (AAC) devices can be an important support. We evaluated the effectiveness of one AAC programme, the Language Acquisition through Motor Planning (LAMP) using a Vantage Lite™ device as the speech output in the home and school environments. Eight children with limited communication were assessed by a speech pathologist prior to the introduction of the programme, after five weeks of training and again after a further two weeks of use of the programme, but without the supported training. The pre-/post-assessment measures revealed that all eight children made gains in the development of spontaneous communication using the device during the implementation period. Parents and teachers also reported that the gains achieved during the five-week trial were greater than those achieved in previous interventions. Two years after the completion of the study, a follow-up phone interview was completed which identified that children who received ongoing support from a LAMP-trained speech pathologist continued using the LAMP programme. As a result of this study, a specialised LAMP specific classroom was established in one of the participating schools.